Effects of prime-boost strategies on the protective efficacy and immunogenicity of a PLGA (85:15)-encapsulated Chlamydia recombinant MOMP nanovaccine - Sahu, Rojalin (2024)
To begin to optimize the immunization routes for our reported PLGA-rMOMP nanovaccine [PLGA-encapsulated Chlamydia muridarum (Cm) recombinant major outer membrane protein (rMOMP)], we compared two prime-boost immunization str ate gies [subcutaneous (SC) and intramuscular (IM-p) prime routes followed by two SC-boosts)] to evaluate the nanovaccine-induced protective efficacy and immunogenicity in female BALB/c mice. Our results showed that mice immunized via the SC and IM-p routes were protected against a Cm genital challenge by a reduction in bacterial burden and with fewer bacteria in the SC mice. Protection of mice correlated with rMOMP-specific Th1 (IL-2 and IFN- γ) and not Th2 (IL-4, IL-9, and IL-13) cytokines, and CD4 + memory (CD44 high CD62L high ) T-cells, especially in the SC mice. We also observed higher levels of IL-1 α, IL-6, IL-17, CCL-2, and G-CSF in SC-immunized mice. Notably, an increase of cytokines/chemokines was seen after the challenge in the SC, IM-p, and control mice (rMOMP and PBS), suggesting a Cm stimulation. In parallel, rMOMP-specific Th1 (IgG2a and IgG2b) and Th2 (IgG1) serum, mucosal, serum avidity, and neutralizing antibodies were more elevated in SC than in IM-p mice . Over all, the homologous SC prime-boost immunization of mice induced enhanced cellular and antibody responses with better protection against a genital challenge compared to the heterologous IM-p.